h - Bubak, Marian; Szepieniec, Tomasz; Wiatr, Kazimierz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The PL-Grid was established to provide the Polish scientific community with a grid-based e-infrastructure, enabling the integration of experimental data and results of advanced computer simulations carried out by geographically distributed research teams. The 26 papers presented in this state-of-the-art survey describe the experience and scientific results obtained by researchers involved in the PL-Grid project. Topics covered include: integration of grid middleware; service operations; security mechanisms; infrastructure monitoring, storage provisioning, and integration of service level agreements; and training and dissemination. In addition, five chapters focus on the application of the PL-Grid middleware and infrastructure to current scientific problems such as grain morphology analysis, chemistry computations, and molecular dynamics modes. The book is rounded off with a useful glossary of terms.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Software Engineering; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices